Answered

Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

If f(x) = 2x² +2 and g(x)=x²-1, find (f- g)(x).

Sagot :

yxzdxn
(f-g)(x) is f(x)-g(x) so
(2x^2+2) - (x^2-1)= 2x^2+2-x^2+1=x^2+3